2020
DOI: 10.1016/j.pss.2019.104825
|View full text |Cite
|
Sign up to set email alerts
|

The morphological, elastic, and electric properties of dust aggregates in comets: A close look at COSIMA/Rosetta’s data on dust in comet 67P/Churyumov-Gerasimenko

Abstract: The Cometary Secondary Ion Mass Analyzer (COSIMA) onboard ESA's Rosetta orbiter has revealed that dust particles in the coma of comet 67P/Churyumov-Gerasimenko are aggregates of small grains. We study the morphological, elastic, and electric properties of dust aggregates in the coma of comet 67P/Churyumov-Gerasimenko using optical microscopic images taken by the COSIMA instrument. Dust aggregates in COSIMA images are well represented as fractals in harmony with morphological data from MIDAS (Micro-Imaging Dust… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
14
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 86 publications
5
14
1
Order By: Relevance
“…Our data indicate that more complex organic materials (humic acid, coal) possess a lower tensile strength than simpler organic materials (graphite, humic acid). This seems to be in contrast to the findings of Kimura et al (2020a) that increasing carbonisation decreases the impact velocity for fragmentation. The latter should be proportional to the square root of the surface energy, which, in turn, is propor- Figure 5.…”
Section: Discussion and Applications To Cometscontrasting
confidence: 99%
See 1 more Smart Citation
“…Our data indicate that more complex organic materials (humic acid, coal) possess a lower tensile strength than simpler organic materials (graphite, humic acid). This seems to be in contrast to the findings of Kimura et al (2020a) that increasing carbonisation decreases the impact velocity for fragmentation. The latter should be proportional to the square root of the surface energy, which, in turn, is propor- Figure 5.…”
Section: Discussion and Applications To Cometscontrasting
confidence: 99%
“…In a recent work, Kimura et al (2020b) showed that the tensile strength of dust aggregates decreases with increasing volume of the object, which depends on the so-called Weibull modulus, a parameter that describes the variability of the material strength. The minimum tensile strength of the organic matter of cometary interplanetary dust particles with an aggregate diameter of ∼ 5 µm was estimated by Flynn et al (2013) to be ∼ 150 to 325 Pa. Kudo et al (2002) found the tensile strength of organic coating on copper spheres to be 10 5 Pa. Data from the COSIMA instrument onboard Rosetta was recently interpreted by Kimura et al (2020a) who found a reduction of the sticking and fragmentation threshold velocity by a carbonisation of the organic matter.…”
Section: Introductionmentioning
confidence: 99%
“…Such a trendy assumption led Dr ażkowska & Alibert (2017) to propose planetesimal formation by the "traffic jam" effect at the snow line, provided that sticky water ice particles grow faster and thus drift toward the central star faster than less-sticky bare silicate particles, implying that aggregates of the former catch up the latter at the snow line, which results in a traffic jam. However, we argue that the importance of water ice to dust coagulation is still open to debate, since water ice is not necessarily stickier than other materials such as silicates and complex organic matter (Kimura et al 2015(Kimura et al , 2020aMusiolik & Wurm 2019).…”
Section: Introductionmentioning
confidence: 91%
“…where γ a is the surface energy of a solid in amorphous phase. We assume γ a = 0.114 J m −2 and dσ/dT = 0.142 mN m −1 K −1 by extrapolating currently available experimental data on the surface tension of ordinary water to low temperatures (Kimura et al 2020a).…”
Section: Tribologymentioning
confidence: 99%
“…On the contrary, if olivine emission peaks were to remain in the infrared spectra of large non-porous particles for whatever reason, a lack of the peaks in the infrared spectra of cometary comae would be attributed to the deficit of olivine in cometary dust. It is, however, highly unlikely that the abundances of silicate in dust particles greatly differ from comet to comet, because the elemental abundances of dust particles in the comae of comets 1P/Halley, 81P/Wild 2, and 67P/Churyumov-Gerasimenko are all solar and very much alike (Kimura et al 2020a). Nevertheless, by considering that articles on small-particle absorption spectra written a half century ago might be nowadays consigned to oblivion, it might be good timing to readdress the Fröhlich mode and reaffirm that large non-porous particles fail to retain twin peaks of olivine in their thermal mid-infrared spectra.…”
Section: Introductionmentioning
confidence: 99%